The role of international human rights law and international criminal law in the construction of the concept of human dignity - Tonetto, Fernanda Figueira (2024)
The present study aims to address the complexity of the task of defining the concept of human dignity, despite this being a central foundation of national and international normative texts. In this sense, human dignity is presented as a universal value that cuts across global legal systems, which reflects the need to protect the irreducible human nature. From this perspective, the development of international human rights law and international criminal law will be examined, with a view to exploring how discrimination, wars and crimes influenced this development and, in the end, trying to identify the future challenges of protection of human rights.